Efficiency of fluorescent cholangiography during laparoscopic cholecystectomy for subvesical bile ducts: A case report. (2019) - Kitamura, Hirotaka; Tsuji, Toshikatsu; Yamamoto, Daisuke; Takahashi, Tohru; Kadoya, Shinichi; Kurokawa, Masaru; Bando, Hiroyuki
Highlights: The subvesical bile ducts are important from the potential risk for bile leakage. It is difficult to identify the subvesical bile ducts intraoperatively. Fluorescent cholangiography visualized the subvesical bile ducts clearly. Abstract: Introduction: The subvesical bile ducts are located in the peri-hepatic connective tissue of the gallbladder fossa. Injury of the subvesical bile ducts provokes the severe complication of bile leak. Until now, fluorescent cholangiography has been employed during hepatobiliary surgery. Herein, we report the detection of subvesical bile ducts by fluorescent cholangiography during laparoscopic cholecystectomy. Presentation of case: A 63-year-old female was admitted to our department for surgery for symptomatic cholelithiasis. The subvesical bile ducts were not observed on drip-infusion cholangiography with computed tomography. Immediately following induction of anesthesia, 2.5 mg of indocyanine green was intravenously injected. Fluorescent cholangiography demonstrated two thin aberrant bile ducts during dissection of Calot's triangle. We considered them to be subvesical bile ducts. We ligated them with clips, divided them, and then performed laparoscopic cholecystectomy using a standard procedure. The patient had a good post-operative recovery without bile leakage. Postoperative laboratory test results were all within normal limits. Computed tomography revealed no dilatation of the intrahepatic bile duct after laparoscopic cholecystectomy. The patient was discharged on postoperative day 4. Discussion: Injury to the subvesical bile ducts is one of the most common causes of bile leakage associated with cholecystectomy. Fluorescent cholangiography enabled real-time identification of the thin subvesical bile ducts, which were undetectable by drip-infusion cholangiography with computed tomography. Conclusion: Fluorescent cholangiography during laparoscopic cholecystectomy may be useful for preventing postoperative bile leakage.